INCLUSIVE ENGLISH EDUCATION: EMPOWERING LEARNERS WITH DISABILITIES THROUGH COOPERATIVE LEARNING APPROACHES - Nor, Hidayah; Asiah, Nur; Saadillah (IAIN Surakarta, 2023)
This research aimed to explore effective cooperative learning strategies for learners with disabilities and identified the challenges teachers face in implementing these strategies in the classroom. A qualitative descriptive approach using a case study design was utilized for data collection, including observations, interviews, and documentation analysis. The collected data was analyzed deductively. The participants of this research were four English teachers and six disabled students of SMAN 4 Banjarbaru, South Kalimantan. The findings of this study revealed that teachers employ various cooperative learning strategies such as NHT (Number Head Together), Jigsaw, Round Robin, and STAD (Student Teams Achievement Divisions) to support students with disabilities. However, teachers encounter specific obstacles in implementing these strategies, including the unique characteristics of each student with a disability, requiring individualized adaptations. This implies that teaching and learning approaches for students with special needs cannot be standardized, and personalized attention and active involvement from both the teacher and other students are crucial for optimal learning outcomes. Keywords: cooperative learning, inclusive English education, disabled learners, learning strategies